2014
DOI: 10.1007/s10517-014-2590-1
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Serotonin during Ischemia under Conditions of Ischemic Preconditioning

Abstract: We studied the dynamics of interstitial serotonin during local myocardial ischemia under conditions of ischemic preconditioning in Wistar rats. Ischemic preconditioning increased serotonin content in the dialysate (p=0.003). During 30-min ischemia, ischemic preconditioning delayed serotonin increase just before the 20th min of ischemia. Ischemic preconditioning promoted short-term increase in the serotonin level in the myocardial interstitium but followed by prolonged ischemia, it delayed the accumulation of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The authors hypothesized that serotonin released by mast cells and sympathetic nerve endings could be responsible for deleterious effects resulting from 5‐HT2A receptor activation during myocardial ischemia, whereas extracardiac serotonin, on the contrary, could elicit protective vasodilatation in the I/R injury context. Naumenko et al reported peak serotonin levels in the myocardial interstitium immediately after preconditioning in a rat model. Serotonin interstitial concentrations increased during ischemia and reperfusion in both preconditioned and control rats, with a more pronounced increase observed in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that serotonin released by mast cells and sympathetic nerve endings could be responsible for deleterious effects resulting from 5‐HT2A receptor activation during myocardial ischemia, whereas extracardiac serotonin, on the contrary, could elicit protective vasodilatation in the I/R injury context. Naumenko et al reported peak serotonin levels in the myocardial interstitium immediately after preconditioning in a rat model. Serotonin interstitial concentrations increased during ischemia and reperfusion in both preconditioned and control rats, with a more pronounced increase observed in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia refers to a decrease in blood perfusion in the heart, resulting in conditions such as hypoxia and abnormal energy metabolism [15,16]. CHD is the main cause of myocardial ischemia.…”
Section: Discussionmentioning
confidence: 99%